Effect of a honey-sweetened beverage on muscle soreness and recovery of performance after exercise-induced muscle damage in strength-trained females - Hemmati, Hadis; Alkasasbeh, Walaa Jumah; Hemmatinafar, Mohammad; Salesi, Mohsen; Pirmohammadi, Sepideh; Imanian, Babak; Rezaei, Rasoul (Frontiers in Physiology, 2024)
Background: This study explores a novel approach to mitigating delayed-onset muscle soreness (DOMS), a common issue among strength-trained females. By investigating the potential of a honey-sweetened beverage, which contains anti-inflammatory properties, we aim to enhance muscle recovery after exercise-induced muscle damage (EIMD).Method: A randomized, cross-over, placebo-controlled, and double-blinded study was conducted with sixteen female strength athletes. Firstly, the baseline measurements were recorded, and participants were randomly divided into two conditions: honey-sweetened beverage (HSB; 70 grams of honey in 250 ml water with a concentration of 28%) and placebo (PLA; 250 ml of water with 70 grams of artificial sweetener). The HSB and PLA were consumed 90 minutes before the EIMD started (200 vertical jumps with 10% body-weighted vests). Recovery monitoring of performance indicators and DOMS was performed after EIMD. The results of wall-sit, V sit and reach (VSFT), vertical jump height (VJH), pressure pain threshold (PPT), and one repetition maximum (IRM) tests were recorded 48 hours after EIMD. Also, DOMS was recorded using the visual analog scale (VAS) before the start of the test and immediately, 12, 24, and 48 hours after EIMD. A one-week interval was considered a washout period for each condition. The collected data were analyzed by repeated measures of ANOVA and Bonferroni post hoc test and dependent t-test at P≤0.05 level.Results: Compared to PLA, HSB ingestion improves wall-sit performance (p=0.003), 1RM (p=0.019), and RPE (p=0.003) after EIMD. However, no significant differences were observed between BL, PLA, and HSB in VJH (p=0.384), VSFT (p=0.840), and PPT (p=0.151) after EIMD. Furthermore, HSB, compared to PLA, considerably decreased the values of DOMS immediately, 12, 24, and 48 hours after EIMD (p˂0.05).Our findings illustrated that ingesting HSB in strength-trained females can be a helpful strategy for improving recovery indicators such as muscle strength, endurance, and muscle soreness after EIMD.